Testicular Biometry, Body-weight, Seminal Attributes and their Correlations in Murrah Bulls - Saurabh; Srivastava, Sushant; Singh, Bhoopendra; Alam, Kabir; Kumar, Rajesh; Kumar, Rabindra; Sharma , Pushkar (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The present study was carried out to evaluate the testicular markers and their correlations with body-weight and seminal output in Murrah bulls. Semen samples were collected from eight Murrah buffalo bulls, aged 4 to 8 years, maintained at the bull station of deep-frozen semen lab of Veterinary College, Faizabad (Uttar Pradesh), India. Biometrical (scrotal circumference, testicular length, testicular diameter, and testicular volume) evaluation was performed by Vernier caliper and scrotal tape in all experimental bulls. The overall mean (± SE) body-weight, scrotal circumference, right testicular length, left testicular length, right testicular diameter, left testicular diameter, pooled testicular volume, ejaculate volume, sperm concentration, and sperm count per ejaculate of Murrah bulls were 716.5 ± 0.59 kg, 34.37 ± 0.41 cm, 11.85 ± 0.12 cm, 12.32 ± 0.14 cm, 7.81 ± 0.07 cm, 8.26 ± 0.08 cm, 791.4 ± 22.62 cm3, 3.82 ± 0.12 mL, 1271 ± 22.68 million/mL, and 4852 ± 166.3 million with significant differences (p<0.01) among the bulls. Left testis was significantly larger than the right one. There were strong correlations between scrotal circumference, testicular length, testicular diameter, testicular volume, and body-weight. The scrotal circumference was significantly (p <0.01) and positively correlated with body-weight (r=0.88), right testicular length (r=0.79), left testicular length (r=0.81), right testicular diameter (r=0.66), left testicular diameter (r=0.75), testicular volume (r=0.79), and had weak correlations (p <0.05) with sperm count (r=0.25) and ejaculate volume (r=0.25). The testicular volume was significantly (p<0.01) and positively correlated with body-weight, ejaculate volume, and total sperm output.